LOCAL AND ECONOMIC GOVERNMENT AS THE DETERMINANT OF INNOVATION AND ECONOMIC CONDITION: CASE STUDY OF SWEDISH ECONOMY - Prystrom, Joanna (Ekonomia i Prawo. Economics and Law, 2013)
Innovativeness of the economy can be described as a determinant of economic development in the region. Businesses innovative activity results in the possibility of their development. Achieved results are tempting for other companies and lead to the undertaking of innovative activity. This in turn contributes to the economic development in the region. Unfortunately, innovative activity comes up against a variety of difficulties. Institutional support including local and economic government, appears to be indispensable in that case. The aim of this paper is to present the essence of local and economic government as part of the institutional environment, which determines innovativeness of local businesses, and also economic development in the region, for example, the Swedish economy – for years perceived as one of the most innovative and competitive in the world.